불안정 대퇴골 전자간 골절 모형에서 두부골수형 골수내 정의 대퇴경간각과 지연나사 위치에 따른 고정력의 생체역학적 분석 - 송형근 (The Graduate School, Ajou University, 2024)
서론: 대퇴 전자간 골절은 골다공증을 동반한 고령 환자에서 발생 빈도가 높다. 이를 치료하기 위해 사용하는 골수정의 대퇴경간각과 지연나사의 위치에 대해 비교 분석을 진행한 연구는 부족한 실정이다. 따라서 본 연구에서는 골수정의 두 가지 대퇴경간각 과 지연나사의 위치에 따른 생체역학적 평가를 진행하여 안정적인 고정이 가능한 대퇴 경간각과 지연 나사의 위치를 알아보고자 하였다. _x000D_ 연구방법: 본 연구에서는 대퇴 인조골을 사용하여 2mm의 골절 간격을 갖는 A2.2 대 퇴골 전자간 불안정 골절을 일정하게 재현하였다. 이후 125° 및 130°의 대퇴경간각 을 가지는 골수정에 지연나사를 대퇴 경부의 중심부 또는 하단부에 위치시켜 총 4가지 Group으로 골절-내고정 모형을 제작하였다. 125° 대퇴경간각의 골수정에 지연나사를 중심부 또는 하단부에 위치시킨 경우를 Group 1, 2로 설정하였으며, 130° 대퇴경간각 의 골수정에 지연나사를 중심부, 하단부에 위치시킨 경우를 Group 3, 4로 설정하였다. 모든 시편을 one-legged stance를 가정하여 frontal plane에서 25° adduction을 적 용하였으며, sagittal plane에서는 neutral position으로 고정하한 후 mechanical testing machine(MTS 858, MTS system Corp., USA)을 이용하여, 각 Group별 4회 의 역학시험을 수행하였다. 수직 압축 하중은 예비 하중(100N, 20N/min), 동적 하중 (75-750N, 10,000cycles, 2Hz), 정적 하중(10mm/min)의 순서로 실험을 진행하였다. 실험을 통해 수직으로 10mm 변형이 발생한 시점에서의 파괴 강도와 강성도를 측정하 였다. 동적 부하 실험 전후 X-ray 촬영을 통한 지연나사의 움직임을 측정하였다. 대퇴 골두의 X(Rotation), Y(Varus collapse), Z(Retroversion collapse)축 회전변화 측정 을 위해 대퇴골두에 marker를 부착 후 Microscribe M (Revware Inc., USA)을 이용 하여 3차원 좌표를 측정하였다. _x000D_ 결과: 정적 압축 실험의 결과는 Group Ⅱ가 1350±64N (Group Ⅰ=1312±100N, Group Ⅲ=1316±98N, Group Ⅳ=1327±92N)으로 가장 높은 파괴강도와 강성도 188±15N/mm (Group Ⅰ=170±3N/mm, Group Ⅲ=173±2N/mm, Group Ⅳ=183 ±7N/mm)를 나타내었다. 또한 실험 전후 X-ray 촬영을 통한 지연나사의 sliding은 Group Ⅱ가 0.54±0.11mm(Group Ⅰ=0.64±0.11mm, Group Ⅲ=0.62±0.11mm, Group Ⅳ=0.56±0.07mm)로 가장 낮은 sliding을 보였다. 그러나 X, Y, Z축 회전변화 의 경우 Group Ⅱ에서 각 1.72±0.09°, 2.25±0.27°, 0.58±0.21°(Group Ⅰ =1.42±0.19°; 1.94±0.41°; 0.51±0.12°, Group Ⅲ=1.33±0.17°; 1.94±0.25°; 0.49±0.15°, Group Ⅳ=1.66±0.18°; 1.97±0.44°; 0.58±0.14°)로 가장 높은 변화를 보였다. 모든 결과는 통계적으로 유의한 차이를 보였다._x000D_ 결론: 본 연구의 결과를 통해 Group Ⅱ에 해당하는 125° 대퇴경간각의 골수정을 이 용해 지연나사를 경부 하단에 위치시킬 때 다른 Group보다 우수한 파괴강도와 강성도 를 갖는 것을 확인할 수 있었다. 그러나 지연나사가 하단부에 위치할 경우 최대 약 30% 높은 회전변화를 보였다. 따라서, 추후 회전변화를 제어할 수 있는 방법에 대한 추가적 인 연구를 수행할 필요가 있을 것으로 사료된다.|Introduction: Intertrochanteric fractures of the femur are a prevalent occurrence among elderly individuals afflicted with osteoporosis. Nevertheless, there exists a notable paucity of research endeavors focused on the comparative analysis of the femoral neck angle and the optimal lag screw placement for the treatment of these fractures. Consequently, the principal aim of this investigation was to undertake a biomechanical assessment, utilizing two distinct femoral neck angles and varying lag screw positions in intramedullary nailing, with the ultimate goal of ascertaining the most stable fixation configuration. _x000D_ Methods: Within the confines of this study, an unstable A2.2 intertrochanteric fracture, characterized by a 2mm interfragmentary gap, was meticulously replicated using artificial femurs as a consistent model. Four discrete fracture-fixation models were devised, predicated on the placement of lag screws either in the central or lower region of the femoral neck. These models were implemented using intramedullary nails featuring femoral neck angles of 125° and 130°, thereby constituting Groups 1, 2, 3, and 4, respectively. Each specimen underwent a series of four mechanical assessments while assuming a one-legged stance with a 25° frontal plane adduction angle and maintaining a neutral position in the sagittal plane. Mechanical evaluations were executed in a sequential fashion, commencing with a preload phase (100N, 20N/min), followed by dynamic loading (75-750N, 10,000 cycles, 2Hz), and culminating with static loading (10mm/min). Fracture strength and stiffness were determined at the juncture where a 10mm vertical deformation was observed. The movement of lag screws before and after dynamic loading was quantified through X- ray imaging. Furthermore, rotational alterations in the femoral head along the X (Rotation), Y (Varus collapse), and Z (Retroversion collapse) axes were assessed. For this purpose, markers were affixed to the femoral head, and their three-dimensional coordinates were recorded employing a Microscribe M (Revware Inc., USA)._x000D_ Results: The outcomes of static compression testing unveiled that Group 2 exhibited the highest fracture strength (1350±64N) and stiffness (188±15N/mm) in contrast to Group 1 (1312±100N, 170±3N/mm), Group 3 (1316±98N, 173±2N/mm), and Group 4 (1327±92N, 183±7N/mm). Furthermore, the displacement of lag screws, assessed via X-ray imaging both pre- and post-testing, demonstrated the least amount of movement within Group 2 (0.54±0.11mm) when juxtaposed with Group 1 (0.64±0.11mm), Group 3 (0.62±0.11mm), and Group 4 (0.56±0.07mm). Conversely, rotational changes about the X, Y, and Z axes were most pronounced within Group 2, with respective values of 1.72±0.09°, 2.25±0.27°, and 0.58±0.21°, in contrast to Group 1 (1.42±0.19°, 1.94±0.41°, 0.51±0.12°), Group 3 (1.33±0.17°, 1.94±0.25°, 0.49±0.15°), and Group 4 (1.66±0.18°, 1.97±0.44°, 0.58±0.14°). _x000D_ Conclusion: The findings of this study underscore the superiority of employing intramedullary nails with a femoral neck angle of 125° in conjunction with lag screws positioned in the lower region of the femoral neck (Group 2), resulting in enhanced fracture strength and stiffness when compared to other configurations. Nevertheless, it is imperative to note that the placement of lag screws in the lower region was associated with a significantly greater rotational change, amounting to approximately 30%. Therefore, future investigations are warranted to explore strategies for mitigating rotational changes in such instances.
학위논문(박사)--의학과,2024. 2
Keywords: 골수정; 대퇴경간각; 대퇴골 전자간 골절; 지연나사